Peran Penyair Didong Gayo Dalam Strategi Dakwah Budaya Lokal - Ihwan, Riski; Habibi, Khairul; Fakhri, Fakhri (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2025)
Amidst the challenges of modernization and the waning interest in conventional da'wah methods, local culture-based da'wah has emerged as an increasingly relevant approach, one of which is through the traditional art of Didong Gayo. This study aims to explore the key role of Didong poets in conveying Islamic messages to the Gayo community in Central Aceh, Bener Meriah, and Gayo Lues. Using a qualitative descriptive approach, data were obtained through in-depth interviews, direct observation, and documentation of poetry texts from various Didong performances. The analysis process was carried out by reducing data, grouping main themes, and interpreting meanings based on cultural communication theory and the concept of da'wah bil hikmah, namely a da'wah method that emphasizes wisdom, gentleness, and adaptation to local wisdom, as well as delivering messages politely and persuasively. The findings indicate that Didong poets play a role as social and moral figures who convey messages of faith, morals, social interactions, and motivation in the form of artistic and communicative poetry. Didong becomes a medium that not only entertains but also builds collective spiritual awareness in society. This research supports the understanding that da'wah through traditional arts can bridge Islamic teachings with local wisdom and open up space for the development of contextual and relevant da'wah strategies in the current era. Further research is recommended to further examine Didong's impact on the younger generation and its potential for transformation in the digital realm.